Perlindungan Hukum Pencegahan Perundungan (Bullying) Di Lembaga Pendidikan Perspektif Maslahat - Aminudin, Aminudin; Panjaitan, Budi Sastra (Universitas Islam Sumatera Utara, 2024)
This paper discusses about legal protection to prevent bullying in schools or better known as school bullying. bullying has long occurred in Indonesia, including in educational institutions. education institutions. The media even reported that it has become an emergency in schools in Indonesia. schools in Indonesia The Indonesian state's responsibility towards bullying prevention is implemented by national laws such as the Child Protection Law and Minister of Education and Culture Regulation Minister of Education and Culture Regulation No.82/2015, but its implementation as a concern is still very specific and limited by laws, changes in norms and behavior through cooperation between the government and all elements. cooperation between the government and all elements. This research uses qualitative approach to identify the factors that cause bullying and its prevention. Materials were obtained from literature and empirical studies about the experience of bullying in junior and senior high school students and all information related to bullying prevention. related to bullying prevention. This research aims to find out how legal policy to prevent bullying in schools in educational institutions in such a way that it is in such a way that it creates maslahat and is useful to prevent and avoid bullying in all its forms. and avoid bullying in all its forms both in the educational environment and in society. education and in society. Keywords: Law, Prevention, Bullying, Institutions Islamic Education Institution, Maslahat 1 Dosen Fakultas Syari’ah Institut Agama Islam Daar Al Uluum Asahan Keywords: Law, Prevention, Bullying, Institutions Islamic Education Institution, Maslahat